Compared to limb pain of other origin, ultrasonographic osteodensitometry reveals loss of bone density in complex regional pain syndrome. Issue 6 (June 2019) - Bazika-Gerasch, Bojana; Maier, Christoph; Kumowski, Nina; Fiege, Carolin; Kaisler, Miriam; Vollert, Jan; Dietrich, Johannes W.
Abstract : Abstract: Local osteopenia and altered bone metabolism are major complications of complex regional pain syndrome (CRPS), but quantitative assessment is difficult unless using X-ray or dual-energy X-ray absorptiometry. Ultrasound-based measurement of bone density (UBD) is a possible alternative but has never been used to detect unilateral disease such as CRPS. Therefore, the main outcome measure of this prospective study was the diagnostic utility of UBD in patients with lower-limb CRPS. Second, we compared the extent of unilateral and contralateral calcaneal bone density to that of other conditions with unilateral pain, general osteoporosis, and healthy subjects. Calcaneal osteodensitometry was bilaterally examined using ultrasound-based methodology. Bone mineral density values were converted to Z-scores based on age- and sex-dependent reference values. All patients completed a functional and an osteoporosis risk questionnaire. In patients with CRPS (n = 18), the bone mineral density values and Z-scores were significantly lower in both the affected (mean ± SD: 0.40 ± 0.08 and −1.1 ± 0.8, respectively) and nonaffected (0.46 ± 0.09 and −0.6 ± 0.9, respectively) limbs than in patients (n = 40) with other unilateral pain syndromes (affected: 0.51 ± 0.1 and −0.2 ± 1.1, respectively; nonaffected: 0.54 ± 0.11 and 0 ± 0.9, respectively) and healthy subjects (right side: 0.6 ± 0.1 and 0.1 ± 0.9, respectively). Conversely, in patients with known systemic osteoporosis, the Z-scores were lower bilaterally with smaller side-to-side differences than in those with CRPS ( P < 0.05). Compared with subjects suffering from long-term CRPS (≥2.4 years), patients with shorter disease duration exhibited significantly lower Z-scores ( P < 0.05). In conclusion, UBD revealed that CRPS is associated with both local and systemic alterations of bone metabolism. Abstract : Supplemental Digital Content is Available in the Text.Ultrasound-based measurement of bone density, a noninvasive and risk-free method, delivers physiological insights and may help to distinguish complex regional pain syndrome from pain of other origin.